Model of Education for Children in Using Health Internet - D. Claretta; Candrasari; I. D. Arianto (Nusantara Science and Technology Proceedings)
The results of research by Yahoo and Taylor Nelson Sofres Indonesia show that the biggest access in Indonesia is those between the ages of 13-19 years. On average children use the internet for 3-4 hours a day, meaning there is a tendency for children to be highly dependent on the internet. This research is needed to contribute to Mother about how to educate so that children can use the internet in a healthy and productive manner. That the mother acts as an educator, directing, encouraging and considering children's behavior and shaping children's behavior. As said in Computer-Mediated-Communication Theory that computers have changed the form of human social relations. This has social and cultural consequences in human life. Technological Cultural Theory states that technology will bring about changes in values and culture in human life. This research was conducted using qualitative methods using the analysis unit of mother and child as research subjects. Data collection techniques were carried out using the Focus Group Discussion method while data analysis techniques used descriptive analysis. The results of this study indicate that the form of education that can be done by the mother is to protect and empower children in using the internet. The success of this educational model can be done well if it becomes part of the parenting style in the digital era.